Groundwater fluoride contamination, probable release, and containment mechanisms: a review on Indian context - Mukherjee, Indrani; Singh, Umesh Kumar (Environmental geochemistry and health, 2018)
Fluoride contamination in the groundwater has got great attention in last few decades due to their toxicity, persistent capacity and accumulation in human bodies. There are several sources of fluoride in the environment and different pathways to enter in the drinking water resources, which is responsible for potential effect on human health. Presence of high concentration of fluoride ion in groundwater is a major issue and it makes the water unsuitable for drinking purpose. Availability of fluoride in groundwater indicates various geochemical processes and subsurface contamination of a particular area. Fluoride-bearing aquifers, geological factors, rate of weathering, ion-exchange reaction, residence time and leaching of subsurface contaminants are major responsible factors for availability of fluoride in groundwater. In India, several studies have reported that the groundwater of several states are contaminated with high fluoride. The undesirable level of fluoride in groundwater is one of the most natural groundwater quality problem, which affects large portion of arid and semiarid regions of India. Rajasthan, Andhra Pradesh, Telangana, Tamil Nadu, Gujarat, and West Bengal are the relatively high-fluoride-contaminated states in India. Chronic ingestion of high doses of fluoride-rich water leads to fluorosis on human and animal. Over 66 million Indian populations are at risk due to excess fluoride-contaminated water. Therefore, groundwater contamination subject to undesirable level of fluoride needs urgent attention to understand the role of geochemistry, hydrogeology and climatic factors along with anthropogenic inputs in fluoride pollution.